The role of organizational culture in implementing improvements General Administrative Officer performance of regional Secretariat North Paser District - Hadiyatno, Didik (CV. Inara, 2021)
Assistant General Administration is the organizational structure under the district secretary in charge of assisting the district Secretary in the implementation of local government. One way to realize the implementation of optimal governance is to demonstrate the performance of its employees. Performance is influenced by several factors including organizational culture, work discipline, leadership style, etc. Research aims to analyze the influence of organizational culture, work discipline and leadership style as a partial or simultaneous to the performance of assistant officers of the public administration of the District secretariat of the North Paser district. The sample in this study was 160 employees who were civil servants (PNS) at the assistant to the General administration of the regional secretariat of the North Paser district office as respondents.English translation. Using multiple linear regression analysis method. The research shows that organizational culture, working discipline and simultaneous leadership style have a positive and significant impact on employee performance. The test results of partial significance from analysis and research studies show that organizational culture, work discipline and leadership style have a positive and significant influence on employee performance and organizational culture has influence the dominant performance of the three factors investigated.